Work as a human, a social value, and a developmental necessity - Bensemcha, Amel; Dhib, Mohammed (The International tax journal, 2026)
Currently, a new attitude toward work is emerging, marked by heightened competitiveness, an overreliance on technology, and a dismissive stance toward simpler occupations. This viewpoint neglects the reality that work is fundamentally rooted in essential human and social values, and that every occupation holds a distinct and significant position within society, offering indispensable services to the community. Therefore, reaffirming these values is crucial to ensure that the development process proceeds correctly and remains as sustainable as possible. This imperative is driven by the emphasis on local development, which is intrinsically dependent on work and production. Work represents material resources and encompasses the fulfillment of both essential and supplementary needs for the individual and his family, resulting in a level of satisfaction that enables the attainment of the quality of life required in contemporary times. This article seeks to address this issue by adopting a comprehensive perspective on human economics and by providing an in-depth analysis of the concept of work.